2011
DOI: 10.1093/hmg/ddr569
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a chronic obstructive pulmonary disease genetic determinant that regulates HHIP

Abstract: Multiple intergenic single-nucleotide polymorphisms (SNPs) near hedgehog interacting protein (HHIP) on chromosome 4q31 have been strongly associated with pulmonary function levels and moderate-to-severe chronic obstructive pulmonary disease (COPD). However, whether the effects of variants in this region are related to HHIP or another gene has not been proven. We confirmed genetic association of SNPs in the 4q31 COPD genome-wide association study (GWAS) region in a Polish cohort containing severe COPD cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
144
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(153 citation statements)
references
References 49 publications
8
144
1
Order By: Relevance
“…Motivated by human GWAS studies showing that HHIP is associated with both COPD affection status in case-control studies and FEV 1 levels in general population samples (12,13), we demonstrate that HHIP protects aging-related airspace enlargement and increases in lung compliance in mice. Reduction in HHIP expression in COPD lungs (16), as well as in lungs of aging rodents (23), increases susceptibility to develop emphysema during aging. Furthermore, reduced antioxidant capacity and increased oxidant levels in Hhip +/− mice preceded emphysema development.…”
Section: Hhip Interacts With Gstp1 and Enhances Glutathione-conjugatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Motivated by human GWAS studies showing that HHIP is associated with both COPD affection status in case-control studies and FEV 1 levels in general population samples (12,13), we demonstrate that HHIP protects aging-related airspace enlargement and increases in lung compliance in mice. Reduction in HHIP expression in COPD lungs (16), as well as in lungs of aging rodents (23), increases susceptibility to develop emphysema during aging. Furthermore, reduced antioxidant capacity and increased oxidant levels in Hhip +/− mice preceded emphysema development.…”
Section: Hhip Interacts With Gstp1 and Enhances Glutathione-conjugatingmentioning
confidence: 99%
“…Therefore, increased cell death and senescence detected in lungs from Hhip +/− mice may result from a combination of autonomous and paracrine effects in multiple cell types. Although more work is needed to characterize autonomous and paracrine effects of HHIP in lungs during aging, it is noteworthy that the increased oxidant burden and increased lymphoid aggregates accompanied by lung function abnormalities in adult Hhip +/− mice recapitulate those seen in human COPD patients carrying risk alleles in the HHIP GWAS locus (16,22).…”
Section: Hhip Interacts With Gstp1 and Enhances Glutathione-conjugatingmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Zhou and colleagues demonstrated a potential role for the HHIP locus in COPD pathogenesis through a series of functional analyses, integrating genetic and molecular biology techniques. 43 They first demonstrated a significant association between the previously identified upstream variant and severe COPD in a cohort of Caucasian smokers from Poland. They then demonstrated reduced HHIP expression in the lung tissue of individuals with COPD compared to smoking controls.…”
Section: Hhipmentioning
confidence: 99%
“…In a previous analysis, we demonstrated that HHIP singlenucleotide polymorphisms (SNPs) were also associated with COPD in a cohort of Polish subjects with severe COPD (12). Given this finding, we examined the relationship between previously reported COPD and lung function GWAS SNPs in this novel population comprised of cases with severe to very severe COPD.…”
mentioning
confidence: 93%